Haematidrosis associated with epilepsy in a girl successfully treated with oxcarbazepine: Case report. (April 2015) - Shen, Hongshi; Wang, Zhaoyue; Wu, Tianqin; Wang, Jing; Ren, Chuanlu; Chen, Haifei; Yu, Ziqiang; Don, Wanli
The aetiology and pathological mechanisms involved in the development of haematidrosis (bloody sweat) remain unclear. There is no specific treatment for this disorder. This case report describes the clinical manifestations and treatment of a 9-year-old female with haematidrosis associated with epilepsy. The diagnosis of haematidrosis was confirmed by medical personnel who observed the bleeding and were able to rule out other causes of the bloody exudate. The episodes of bleeding were spontaneous, transient, and self-limited. Smears of the bloody exudate contained all of the components of peripheral blood. A skin biopsy taken at one site of the bloody exudate was normal, showing no signs of blood extravasation or bleeding sweat glands. The bleeding events were found to be immediately preceded by tonic seizures. An electroencephalogram indicated cerebral parietooccipital epilepsy, which was characterized by an intermittent medium-high amplitude θ rhythm (5–7 Hz) with a few spikes. The symptoms of both epilepsy and haematidrosis resolved after treatment with the antiepileptic drug 150 mg oxcarbazepine, orally, twice a day, which suggests that the epileptic seizures triggered haematidrosis in this patient.